Free radical scavenging activity of extracts from seaweeds Macrocystis pyrifera and Undaria pinnatifida: applications as functional food in the diet of prawn Artemesia longinaris - Díaz, Ana Cristina (2017)
Water-soluble extracts from seaweeds Macrocystis pyrifera (M) and Undaria pinnatifida (U) were prepared to use the polysaccharide bioactive fraction as functional food. Chemical analysis showed that the main components of both extracts were mannitol and fucoidans. Also in both cases minor amounts of rhamnose, glucose, xylose and arabinose were determine. Content of fucose+galactose was higher in U. pinnatifida (8.7%) than in M. pyrifera (5.9%). Extracts were used as feed additive to Artemesia longinaris at inclusion levels of 1 and 2% (M1 and M2; U1 and U2), a diet without extract was used as control. Radical scavenging activities were estimated for two extracts and for midgut gland samples of experimental animals. Scavenging activity was detected in both extracts, the signal decayed to 50 and 62% in 18 min for U. pinnatifida and M. pyrifera, respectively. After 30 days of feeding, results did not show variation of survival, but growth was improved in animals fed with U1 and U2. Supplementation with 1 and 2% of U. pinnatifida showed similar quenching capacity of homogenates than those fed with M2 with a rapid 1,1-diphenylpicrylhydrazyl (DPPH) decay at 2 min of reaction. Recommended concentration for culture A. longinaris is 2%, as it is that produce the best antioxidant capacity, although the growth performance was improved also significantly only with U. pinnatifida extract.